Evaluating the water Tigris of the River in Al-Nu'maniya District. (Journal of the College of Basic Education, 2022)
The surface water represented by the Tigris River is the primary and important source for meeting the economic and social needs in the study area, which are affected by several natural and human factors during its passage in the study area and thus its effect on the physical and chemical properties of the river water, which led to the impact on its efficiency and suitability to use it for different purposes.The results of the study showed, through samples taken from different locations of the Tigris River, that they are polluted as a result of wastewater, agricultural and residential homes near the Tigris River as well as groundwater containing salts that the affected waters of the Tigris River in the area. The results of analyzes were compared to samples taken with standards For every use and monthly (January and July), it was found that that many characteristics exceeded those standards, especially irrigation and industrial uses, as well as some of the irrigation classifications were used, the most important of which are the percentage of sodium (Nay), permeability index (pt) and the sodium adsorption ratio (SAR) to know the effect Irrigation water on the soil. Finally, some classifications were used, including the Todd classification, to know the extent of the validity of the Tigris River over human life